Obtenção e caracterização de argilas bentonitas modificadas com Brometo de Hexadeciltrimetilamônio para adsorção de pesticidas organoclorados - SANTOS, Matsvilandel Gonçalves dos (2017)
Organochlorine (OCs) pesticides are persistent, bioaccumulative substances in the food chain, with high mobility in the environment. This is of concern, because vry often these compounds are detected in surface and groundwater, affecting thus quality of water resources and biodiversity. Because of the serious contamination of aquatic ecosystems by OCs, it is necessary to develop new and eficiente adsorbent materials for remediation of already contaminated areas. The objective of this work was to prepare and to characterize organophilic clays chemically treated with the hexadecyltrimethyl-ammonium bromide salt (HDTMA-Br), aiming their use as an adsorbent material for the removal of residues of OCs in the environment. In order to analyze the OCs, was optimized a methodology based on solid phase extraction followed by gas chromatography with electron capture detector (SPE-GC/ECD). The characterization of the material was carried out by determination of the cation exchange capacity (CTC), as well as X-ray diffraction (XRD), infrared spectroscopy (FTIR) and electron microscopy of scanning (SEM). The adsorptive capacity of the organophilic clay was determined by kinetic adsorption tests and adsorption isotherms. Chromatographic method, besides high selectivity, showed adequate linearity (arounding 0.25 to 20.0 µg.L-1), sensitivity (LODs varying from 0.03 to 0.79 µg.L-1 and LOQs varying from 0.13 to 2.63 µg.L-1) and precision for trace analysis (CVs varying between 2.16 to 26.69 µg.L-1). The natural clay presented adequate cation exchange capacity (CTC) for organophilization and the results of the characterization indicated the intercalation of HDTMA salt cations between the intermediate layers of the modified clays. The kinetic adsorption assays performed revealed 125% COC as the best adsorbent, exhibiting affinity for aldrin and 4,4'-DDT pesticides. The experimental data were better fitted to the pseudo-first-order and pseudo-second order model for the 4,4'-DDT and aldrin compounds, respectively. The Langmuir isotherm model described better the adsorption of the 4,4'-DDT compound, whereas the Freundlich model represented better the adsorption of the aldrin compound, indicating a very favorable adsorption condition.